PENGARUH PROFITABILITAS DAN RASIO PENILAIAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR FOOD AND STAPLES RETAILING - Matyani, Matyani; Susilowati, Dwi; Berliana Juwita Rullyanti, Evy (Jurnal GeoEkonomi, 2024)
The purpose of this study was to determine the effect of Return on Equity, Earning Per Share, Price Earning Ratio, and Dividend Payout Ratio on Stock Price. The total population in this study was 13 companies and the sample was 4 companies of food and staples retailing sub sector listed on the Indonesia Stock Exchange that taken by using the criteria determined by the author. The data analysis method used is multiple linear regression. The result of the T test (partial test) showed that Return on Equity, Earning Per Share, and Price Earning Ratio have a positive relation and have a significant effect on Stock Price, while Dividend Payout Ratio has a negative relation and have no significant effect on stock price in food and staples retailing sub sector companies listed on Indonesia Stock Exchange.